My brave year of firsts : tries, sighs, and high fives - Curtis, Jamie Lee, 1958- (Joanna Cotler Books, 2012)
"The tenth children's book by the #1 New York Times bestselling team of Jamie Lee Curtis and Laura Cornell celebrates the extraordinary, everyday bravery of trying new things for the very first time." -- Jacket flap.